NOBLE GASES IN THE MOON AND METEORITES: RADIOGENIC COMPONENTS AND EARLY VOLATILE CHRONOLOGIES - Swindle T.D. (My University, 2002)
One of the reasons noble gases make such good tracers of processes occurring in rocks is their scarcity. Thus, a process that converts a small fraction of a relatively rare element into a noble gas can have a large effect on the noble gas. Radioactive decay can be such a process. In a meteorite which has formed very early in the solar system’s history and been little altered since, the effect can be even more dramatic. Furthermore, since radioactive decay proceeds at a known rate, radiogenic noble gases, those produced by decay, have been crucial in deciphering the chronology of...